Gorgeous Girlies in Glittering Gyrations! Capital érotique et danse jazz dans l’entre-deux-guerres québécois - Blais-Tremblay, Vanessa (Recherches féministes, 2019)
Dans la littérature sur la danse exotique de la première moitié du xxe siècle, la danseuse noire apparaît soit comme la victime d’une industrie du divertissement capitalisant sur les mises en scène érotisantes, exotisantes et primitivisantes de son corps, soit comme la parodie subversive du stéréotype dit « primitif-exotique » incarné sur scène. Pour paraphraser bell hooks, le plaisir corporel, voire charnel, lié à la danse est avant tout abordé en tant que réalité à laquelle il faut résister, qui doit être masquée ou transcendée, ce qui force ainsi un processus de distanciation entre le travail artistique de la danseuse et le capital érotique de son corps. Dans cet article, l’auteure s’appuie sur une collection d’entretiens réalisés dans le contexte du travail de recherche ayant mené à la production cinématographique Show Girls: Celebrating Montreal’s Legendary Black Jazz Scene (1999) avec des danseuses qui travaillaient dans l’industrie du spectacle durant l’« âge d’or » du jazz montréalais (1925-1955). Les récits que révèlent ces entretiens permettent d’aller au-delà des questions de représentation dans la littérature sur la danse exotique pour poser un regard sur l’agentivité artistique de ces femmes qui résistent à la désarticulation entre leur travail artistique et le capital érotique de leurs corps.

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.